Competitive attitudes and psychological and somatic health in old age - Márta, Fülöp (Magyar Gerontológia, 2023)
For a long time, competition in old age has not been a focus of interest for researchers because none of the psychological theories of aging assumed that the motivation to compete persists in old age. The two most prevalent models, the so-called "Deficit Model" (Cumming & Henry, 1961) and the so-called "Integrated Personality Model" (Erikson, 1963), have previously held that the psychological conditions for competition are not present in old age. In contrast, the concept of successful aging (Baltes, 1990), introduced as a consequence of the steady increase in life expectancy, assumes that goals, aspirations, and desires survive into old age.